The influence of experimental learning methods on student interest and learning outcomes in physics lessons - Yardi, Septia Dini (Science, Technology and Communication Journal, 2024)
Classroom action research (CAR) has been carried out with the aim of knowing the level of student achievement after being given an experimental learning method. This is because the experimental learning technique is a way of teaching in which students conduct an experiment about something and observe the process. Write the results of the experiment then the results of the observations are submitted and evaluated by the teacher. The CAR model used is the problem-based learning flow and the Spiral and Taggart models. The results of the evaluation showed that student achievement had increased after the experimental method of learning was compared with conventional learning models.